Mengapa Tataruang Kota Majapahit Berpola Rektangular - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Rectangular spatial pattern of "grid pattern" was invented thousamds years ago in Mohenjo-Daro, and was further adopted by cities in a nuber of countries, namely Mezzo-America and the Niles Valley. India, China, Japan and South-East Asia are the later followers to adopt the pattern. Majapahit, the capital city of Majapahit Kingdom, has also adopted grid pattern when Raden Wijaya, the first king of Majapahit, started to build it in the XIV century on a strategically located fertile Brantas valley, East Java. Theories were set forth to explain why and how grid patterns were further adopted by cities which are very distant in place and time.